Clinical and epidemiological characteristics of hypertrophic pyloric stenosis in a hospital in Lima, Perú. - Torres Guinand, Carlos Guillermo (2022)
Objective: To determine clinical and epidemiological characteristics of hypertrophic pyloric stenosis in a hospital in Lima, Peru. Materials and Methods: A descriptive and retrospective study encompassing years 2013 to 2019 was performed in the Pediatric Surgery Service of San Bartolome Teaching Mother and Child Hospital. Data from clinical records of patients diagnosed with hypertrophic pyloric stenosis was collected. Results: Records from fifty-nine patients were obtained, 79% were male, 68.4% were first born, and their mean age was 31.3 ± 13.6 days. All patients (100 %) had vomit, 44.1% had abnormal abdominal movement, and only 35.6% had palpable pyloric olive. The average surgical correction time was 51.39 minutes, and the average hospital stay was 6.35 days, major complications occurred in 13.6% of all children, and the mortality rate was 3.4%. Conclusions: Early initiation of oral intake is important, as well as post-surgical managementin these patients, in order to reduce their in-hospital stay and the development of post-surgical ventilatory complications.